Micromechanical magnetometer using an all-silicon nonlinear torsional resonator - Antonio, Dario (2009)
In this work, a micromagnetometer employing a nonlinear torsional resonator with a high quality factor Q is presented experimentally. Oscillatory rotation of a conducting plate in the sensed magnetic field H induces eddy currents that dissipate energy. Due to the nonlinear response of the oscillator, the resulting mechanical damping originates frequency shifts in the resonance curve that depend on H. Nonlinearity results from the electrostatic detection, which introduces high order electrical spring constants. The device is fabricated with a standard silicon process and does not incorporate ferromagnetic materials. An analytical nonlinear model that correctly describes the device is also introduced.